Analysis of Disinfection Technologies that can Increase the Efficiency of Indoor Logistics Processes, which has been Reduced due to the COVID Pandemic - Adrienn Boldizsár; Ákos Tóth; Erika Török; Attila Pásztor (International Journal of Engineering and Management Sciences, 2023)
As a result of the Coronavirus, both supply chain and internal logistics processes at factories have changed a lot. In many areas, the effectiveness of the logistics processes has declined because of the restrictions implemented against the virus. The study lists some adverse effects where logistics processes had to be modified due to the changing and protection measures against or negative effects of the virus. The authors also argue that these restrictions decreased the efficiency of logistics processes and workers' productivity. One option to increase the logistics sector's efficiency is to use air purification technologies, like the ones studied in this paper: UV-C, Bioxygen® or plasma-ion decontamination technologies. These disinfection processes can create a safe indoor environment. The authors analyse the examined technologies with SWOT analysis. The analysis results demonstrate which disinfection application is the most beneficial to help in improving indoor air quality for logistics processes.